Pendekatan SAVI (Somatic, Auditory, Visual, Intelectualy) dan Pengaruhnya Terhadap Kemampuan Komunikasi Matematis Siswa Sekolah Dasar - Arifin, Fatkhul; Ervanda, Yosi (Al-Azkiya: Jurnal Pendidikan MI/SD, 2023)
Mathematics learning is often one of the scary lessons for some students. SAVI is one of the solutions to overcome this problem because it is the way students learn, both students who tend to be audi, visual and audio-visual. This study measures the SAVI Approach (Somatic, Auditory, Visual, and intellectual) in Mathematical Communication. Research methods used are experimental quasi using Pre-test and Post-test Nonequivalent Control Group Desain. Studies have shown that the ability of mathematical communication taught by the SAVI approach (somatic, visual, auditory, intellectual) is higher than that of a student-led with a collaborative process. Hypothesis testing was carried out with a significance level of 5%; the results of hypothesis testing on the results of the posttest data using independent t-samples obtained a sig post value of 0.002 <0.05, meaning that H0 was rejected and H1 was accepted. The Savi approach (somatic, visual-auditory, intellectual) teaches the students mathematical communication abilities: 85% of the written text aspects, 69% of drawing aspects, and 79% of the mathematical expression.